1999
DOI: 10.1111/j.1748-7692.1999.tb00804.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Studies of Marine Mammals Using Stable Carbon and Nitrogen Isotopic Ratios of Teeth

Abstract: This study used naturally occurring carbon and nitrogen stable isotopes of teeth to study the diets of marine mammals. The isotopic ratios of nonchemically preserved teeth from eight species of marine mammals, representing 87 individuals that spanned the trophic continuum, were found to reflect nutritional sources. The δ13C signals distinguished animals that lived in waters dominated by different primary producers (e. g., seagrass, kelp, and phytoplankton), and δ15N values indicated the diet and trophic level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 43 publications
2
74
0
Order By: Relevance
“…These values as well as the isotopic signature in liver (δ 13 C = -18.4 ‰ ± 0.3 and δ 15 N = 13.2 ‰ ± 0.6) and muscle (δ 13 C = -19.0 ‰ ± 0.9 and δ 15 N = 14.6 ‰ ± 0.6) of stranded sperm whales in the North Sea (Das et al 2003) are lower than those of adult males in the Gulf of California. Additionally, the stable isotope ratios from a single tooth of a sperm whale, in which sequential dentin layers were analysed, showed that both δ 13 C (-12.1 to -13.8 ‰) and δ 15 N (18.1 to 16.1 ‰) tend to become lower with age (Walker & Macko 1999). Our results are consistent with this finding because the sloughed skin samples from immature males were higher in both δ 13 C and δ 15 N composition compared with those from mature males (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These values as well as the isotopic signature in liver (δ 13 C = -18.4 ‰ ± 0.3 and δ 15 N = 13.2 ‰ ± 0.6) and muscle (δ 13 C = -19.0 ‰ ± 0.9 and δ 15 N = 14.6 ‰ ± 0.6) of stranded sperm whales in the North Sea (Das et al 2003) are lower than those of adult males in the Gulf of California. Additionally, the stable isotope ratios from a single tooth of a sperm whale, in which sequential dentin layers were analysed, showed that both δ 13 C (-12.1 to -13.8 ‰) and δ 15 N (18.1 to 16.1 ‰) tend to become lower with age (Walker & Macko 1999). Our results are consistent with this finding because the sloughed skin samples from immature males were higher in both δ 13 C and δ 15 N composition compared with those from mature males (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These trophic-related isotopic discrimination factors have served as effective tools in prior studies of marine mammal and seabird foraging ecology and habitat use (Schoeninger & DeNiro 1984, Wada et al 1987, Schell et al 1989, Rau et al 1992, Hobson et al 1997, Burton & Koch 1999, Walker & Macko 1999, Kurle & Worthy 2001.…”
Section: Abstract: Orcinus Orca · Stable Isotopes · Weaning · Tooth mentioning
confidence: 99%
“…Stable isotope analysis provides a means of studying past diets through the examination of historic tissue samples such as bones, teeth, and preserved skins in museum collections. Isotopic differences at the base of the food web are passed to higher trophic levels with small, characteristic offsets and have served as natural labels in studies of marine mammal foraging ecology (Schell et al 1989, Ostrom et al 1993, Hobson et al 1997, Burton & Koch 1999, Walker & Macko 1999, Kurle & Worthy 2001. Important to many of these studies is the characteristic increase of ~1 and ~3-5 ‰ in δ 13 C and δ 15 N values respectively with each trophic step, which permits study of food web dynamics and trophic status (DeNiro & Epstein 1978, Minagawa & Wada 1984.…”
Section: Abstract: Northern Fur Seals · Callorhinus Ursinus · Stablementioning
confidence: 99%